Strategic Management: Financial Planning and Fund Management for MSMEs - Sumartan Sumartan; Suriadi Suriadi (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in both the global and local economies by contributing to job creation and innovation. However, MSMEs often face challenges in financial management, including access to financing and cost control. This study examines the importance of strategic financial management for MSMEs, including financial planning, cash flow management, and investment diversification. A qualitative approach is used to explore effective strategies in fund management and identify the challenges faced. The research findings indicate that good financial planning, wise fund management, and investment diversification are key strategies for enhancing MSME competitiveness and sustainability. Practical recommendations are developed to assist MSMEs in achieving their financial goals.